A pH / mg2+ response controlled-release type hydrogen-melatonin composite preparation and its application in chrysanthemum stress relief

CN122997124APending Publication Date: 2026-10-30LULIANG UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611161870.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-03
Publication Date
2026-10-30

AI Technical Summary

Technical Problem

[0006]要解决的技术问题:针对现有富氢水浇灌技术氢气极易衰减、固态氢制剂释氢速率无法自适应调控且易导致土壤pH异常升高、褪黑素田间施用易光降解和淋溶流失、以及现有技术尚未将H2供体与褪黑素整合为信号级联协同体系的技术问题,本发明的目的是提供一种pH/Mg2+响应控释型氢-褪黑素复合制剂及其在菊花逆境胁迫缓解中的应用,构建H2-MT信号级联协同抗逆体系,内源MT诱导与外源MT补充双通道协同,抗逆效果显著超越单独施用H2或MT;实现pH/Mg2+/湿度三因子自适应释氢调控,释氢速率与植物生理需氢节奏自然同步

Benefits of technology

[0017]1、本发明首次将固态H2供体与外源MT整合为协同体系,构建内源MT诱导和外源MT补充双通道褪黑素供给。H2作为上游信号分子上调SNAT基因表达(表11:SNAT表达提升225%),促进内源MT合成(内源MT提升266.4%),低剂量持续外源MT缓释补充弥补重度胁迫下内源MT合成瓶颈,两者协同叠加显著放大抗逆效果。高温胁迫下Pn提升124.5%、MDA降低67.9%、SOD提升96.7%,显著优于单独施用富氢水或MT。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122997124A_ABST
    Figure CN122997124A_ABST
Patent Text Reader

Abstract

The application discloses a kind of pH / Mg 2+ The application discloses a pH / Mg 2+ The application discloses a kind of pH / Mg 2+ The application discloses a kind of pH / Mg 2+ The application discloses a kind of pH / Mg 2+ The application discloses a kind of pH / Mg 2+ The application discloses a kind of pH / Mg 2+ The application discloses a kind of pH / Mg 2+ The application discloses a kind of pH / Mg 2+ The application discloses a kind of pH / Mg 2+ The application discloses a kind of pH / Mg 2+ The application discloses a kind of pH / Mg 2+ The application discloses a kind of pH / Mg 2+ The application discloses a kind of pH / Mg 2+ The application discloses a kind of pH / Mg 2+ The application discloses a kind of pH / Mg 2+ The application discloses a kind of pH / Mg 2+ The application discloses a kind of pH / Mg 2+ The application discloses a kind of pH / Mg 2+ The application discloses a kind of pH / Mg 2+ The application discloses a kind of pH / Mg 2+ The application discloses a kind of pH / Mg 2+ The application discloses a kind of pH / Mg 2+ The application discloses a kind of pH / Mg 2+
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of plant cultivation technology, specifically relating to a pH / Mg... 2+ Response-controlled release hydrogen-melatonin complex formulation and its application in relieving abiotic stress in chrysanthemum. Background Technology

[0002] Chrysanthemum is a medicinal crop of the Asteraceae family with high medicinal value and rich active ingredients. Its growth is sensitive to environmental conditions and easily affected by stresses such as high temperature, drought, and strong light. The synthesis and accumulation of active ingredients such as flavonoids and chlorogenic acid are directly regulated by environmental stress, while the stability of the soil microecology directly determines the yield and quality of chrysanthemums. Hydrogen-rich water irrigation is a newly emerging auxiliary technology for chrysanthemum cultivation in recent years. Hydrogen, as a novel antioxidant, can effectively remove reactive oxygen species in chrysanthemum plants, enhance plant resistance, and promote flower bud differentiation and accumulation of active ingredients. However, existing hydrogen-rich water irrigation technology has significant drawbacks: Firstly, hydrogen molecules are extremely small and highly volatile, and hydrogen-rich water cannot maintain a high concentration for long periods. After several hours of storage, the hydrogen concentration drops sharply, greatly reducing the effectiveness of "hydrogen-rich" irrigation, sometimes making it indistinguishable from ordinary water. Secondly, long-term high-concentration hydrogen-rich water irrigation can alter the natural balance of microorganisms in the soil, affecting soil fertility structure and potentially weakening the chrysanthemum's own defense mechanisms, leading to a decrease in its adaptability to environmental changes.

[0003] Melatonin (MT) is a small indoleamine molecule widely found in plants. In plants, it is synthesized from tryptophan through a four-step enzymatic reaction involving tryptophan, serotonin, and N-acetyl-serotonin, with serotonin N-acetyltransferase (SNAT) being the rate-limiting enzyme. Recent studies have shown that exogenous MT can effectively alleviate various abiotic stresses in chrysanthemums: research has found that foliar spraying of MT can significantly reduce MDA accumulation and H2O2 content in chrysanthemum seedlings under high-temperature stress, increase the activity of antioxidant enzymes such as SOD, POD, CAT, and APX, and promote the synthesis of osmotic regulatory substances such as proline and soluble proteins.

[0004] However, exogenous MT faces severe challenges in field applications: MT is an amphiphilic small molecule that is easily photodegraded under ultraviolet light, and is easily metabolized by microorganisms or leached away by water in the soil. Traditional foliar spraying methods require repeated application and are greatly affected by rainfall, resulting in low utilization efficiency. At the same time, the concentration of MT synthesized by plants themselves is often insufficient to cope with severe stress, while high-concentration exogenous supplementation is difficult to maintain at an effective concentration due to the aforementioned degradation problems. In addition, although existing MT slow-release formulations (such as chitosan microparticles and β-cyclodextrin nanosponges) can delay MT release to a certain extent, they have a single function, only solving the problem of MT delivery, and failing to synergistically integrate MT with other stress-resistance signaling molecules (such as H2), thus failing to exert the stress-resistance effect of signal cascade amplification.

[0005] To address the aforementioned issues, a method with high safety, stable hydrogen release, and the ability to utilize the root zone microenvironment (pH, Mg) is being developed. 2+ The development of a compound formulation that can adaptively regulate the hydrogen release rate (concentration and humidity) and simultaneously release melatonin to exert a synergistic anti-stress effect through the H2-MT signal cascade, while also being simple in process and cost-effective, and its application method for alleviating the stress of chrysanthemum, has become a pressing technical challenge. Summary of the Invention

[0006] The technical problems to be solved are as follows: In existing hydrogen-rich water irrigation technologies, hydrogen decay is extremely easy; the hydrogen release rate of solid hydrogen preparations cannot be adaptively controlled and easily leads to abnormal increases in soil pH; melatonin is prone to photodegradation and leaching loss during field application; and existing technologies have not yet integrated H2 donors and melatonin into a signaling cascade synergistic system. The purpose of this invention is to provide a pH / Mg... 2+ Response-controlled release hydrogen-melatonin complex formulation and its application in alleviating abiotic stress in chrysanthemum: A synergistic H2-MT signaling cascade anti-stress system was constructed, with endogenous MT induction and exogenous MT supplementation working synergistically, resulting in an anti-stress effect significantly exceeding that of H2 or MT alone; achieving pH / Mg... 2+ The three factors of humidity adaptively regulate hydrogen release, and the hydrogen release rate is naturally synchronized with the plant's physiological hydrogen demand rhythm.

[0007] Technical solution: A pH / Mg 2+ A responsive controlled-release hydrogen-melatonin composite formulation, wherein the composite formulation is made by mixing solid hydrogen formulation double-layer coated particles, γ-PGA / melatonin composite controlled-release material and biocompatible binder in a mass ratio of 3~5:1:0.1~0.2, and then forming integrated particles with a diameter of 2~3mm by low-pressure tableting process.

[0008] Furthermore, the preparation steps of the solid hydrogen preparation double-layer coated particles are as follows: (1) Raw material pretreatment: Magnesium hydride micro powder was ball-milled to a particle size of 1~5μm under anhydrous, oxygen-free, and nitrogen-protected conditions; diatomaceous earth was dried to a moisture content of ≤0.5%; (2) Powder mixing: Under a nitrogen atmosphere, first mix 30-38 parts of magnesium hydride micro powder with 15-22 parts of potassium dihydrogen phosphate for 8-10 min, then add 15-25 parts of diatomaceous earth, 10-18 parts of slow-release regulator and 5-10 parts of binder in sequence, and mix at a speed of 50-80 r / min for 25-30 min to obtain composite powder; (3) Dry granulation: The roller pressing dry granulation process is adopted to produce initial particles of 0.5~2mm; (4) Low temperature drying: vacuum drying at 40~45℃ for 2 hours under nitrogen atmosphere, then cooling to room temperature; (5) Double-layer gradient coating: Fluidized bed coating technology is adopted. First, ethyl cellulose ethanol solution is used as the inner hydrophobic coating liquid with a coating thickness of 50~100μm; then, chitosan dilute acetic acid solution is used as the outer hydrophilic coating liquid with a coating thickness of 30~50μm. The outer chitosan layer has both hydrophilicity and pH-responsive shrinkage characteristics, resulting in solid hydrogen preparation double-layer coated particles.

[0009] Furthermore, the sustained-release regulator in step (2) is a mixture of stearic acid and palmitic acid; the binder is hydroxypropyl methylcellulose.

[0010] Furthermore, the mass ratio of stearic acid to palmitic acid is 1:1.

[0011] Furthermore, in step (5), the mass fraction of the ethyl cellulose ethanol solution is 5-8%; and the mass fraction of the chitosan dilute acetic acid solution is 3-5%.

[0012] Furthermore, the preparation method of the γ-PGA (polyglutamic acid) / melatonin composite controlled-release material is as follows: S1. Dissolve melatonin in anhydrous ethanol to prepare a melatonin ethanol solution with a concentration of 100~200 μmol / L; S2. Immerse γ-PGA powder in melatonin ethanol solution and stir for 30 min; S3. Vacuum dry at 30~35℃ for 6-7h to allow ethanol to evaporate completely, melatonin to be uniformly dispersed and physically embedded in the γ-PGA matrix; S4. Grind through a 100-mesh sieve to obtain γ-PGA / melatonin composite controlled-release material powder.

[0013] Furthermore, the liquid-to-solid ratio of melatonin ethanol solution to γ-PGA in S2 is 40~60 mL / g.

[0014] Furthermore, the biocompatible adhesive is gelatin.

[0015] The present invention also provides the above-mentioned pH / Mg 2+ Application of a responsive controlled-release hydrogen-melatonin complex formulation in alleviating abiotic stress in chrysanthemum.

[0016] Furthermore, the application method is as follows: 1. Application timing: Apply every 7-10 days from the time the chrysanthemum is planted until the budding stage; during the flowering period and the period of high temperature and strong light stress, apply every 5-7 days. 2. Application method: Dig a shallow trench 5-10cm deep, 5-8cm away from the base of the chrysanthemum plant, spread the granules evenly in, cover with soil and compact. 3. Application rate: Apply 2-3g per chrysanthemum plant each time; 4. pH monitoring and adjustment: Regularly use a portable pH meter to test the pH of the root zone soil. When the soil pH is >8.0, reduce the application amount or suspend application. Resume application after the soil pH returns to 6.0~7.0. Beneficial effects

[0017] 1. This invention is the first to integrate solid H2 donor and exogenous melatonin (MT) into a synergistic system, constructing a dual-channel melatonin supply system of endogenous MT induction and exogenous MT supplementation. H2, as an upstream signaling molecule, upregulates SNAT gene expression (Table 11: SNAT expression increased by 225%), promotes endogenous MT synthesis (endogenous MT increased by 266.4%), and low-dose continuous exogenous MT supplementation compensates for the bottleneck in endogenous MT synthesis under severe stress. The synergistic effect of both significantly amplifies the stress resistance effect. Under high-temperature stress, Pn increased by 124.5%, MDA decreased by 67.9%, and SOD increased by 96.7%, which is significantly better than the application of hydrogen-rich water or MT alone.

[0018] 2. This invention provides a stable basic hydrogen supply through a double-layer gradient coating (cumulative hydrogen release of 362~398 mL / g over 14 days); the pH-responsive contraction of the chitosan outer layer is self-inhibited under alkaline conditions (hydrogen release decreases to 28%~36% at pH 9.0); γ-PGA's Mg... 2+ Crosslinking provides gradual damping (CV < 5% during peak plateau); γ-PGA humidity positive feedback synchronizes hydrogen release with plant transpiration rhythm (hydrogen release increases by 35%~42% when humidity changes from 25% to 40%). The dynamic balance between positive and negative feedback avoids explosive release or insufficient hydrogen supply.

[0019] 3. In this invention, the γ-PGA matrix provides dual protection for MT: ① physical shielding blocks ultraviolet rays, reducing the photodegradation rate; ② water absorption and swelling followed by dehydration and shrinkage controls the sustained low-dose release of MT (cumulative release rate of 68%~75% over 28 days), avoiding the problems of repeated application and easy leaching and loss of MT when spraying leaves. The release of H2 and MT is regulated by the same humidity response mechanism, with a synchronization index (SI) of 0.92~0.94, achieving temporal synchronization and spatial synergy.

[0020] 4. This invention utilizes pH negative feedback self-regulation and γ-PGA Mg 2+ The triple protection provided by the gradually varying damping and potassium dihydrogen phosphate buffer system ensured that the soil pH remained within the safe range of 6.6–7.1 throughout the process (Table 10), with no abnormal increases. The diatomaceous earth, coating material, γ-PGA, and binder are all biodegradable, leaving no soil residue. Compared to irrigation with high-concentration hydrogen-rich water, which may disrupt the soil's microecological balance, this invention is soil-friendly.

[0021] 5. In this invention, diatomaceous earth is used as an inert filler. Its porous structure has a heat capacity buffering effect and a dilution isolation effect, which effectively reduces the risk of spontaneous combustion of MgH2 dust; the hydrogen release retention rate is >92% after 30 days of accelerated release at 40℃ / 75%RH.

[0022] 6. The process of this invention is simple: dry granulation + low-pressure tableting composite process, no special equipment is required, and it can be mass-produced industrially.

[0023] 7. This invention is easy to apply: the compound granules can be applied to the root zone without the need for complicated irrigation equipment, and can be directly integrated into the existing medicinal chrysanthemum cultivation system. Attached Figure Description

[0024] Figure 1 The cumulative hydrogen release amounts for Examples 1-4 and Comparative Examples 1-4; Figure 2 The average hydrogen release rates for each time period in Examples 1-4 and Comparative Examples 1-4; Figure 3 The cumulative amount of water permeation in Examples 1-4 and Comparative Examples 1-4 is given. Detailed Implementation

[0025] Other materials used in this invention, unless otherwise stated, are commercially available. Other terms used in this invention, unless otherwise specified, generally have the meanings commonly understood by those skilled in the art. The invention is further described in detail below with reference to specific embodiments and data. The following embodiments are merely illustrative and not intended to limit the scope of the invention in any way.

[0026] The degree of deacetylation of the chitosan used below is 90%; the mass fraction of the acetic acid solution is 1.5%; and the weight-average molecular weight of polyglutamic acid (γ-PGA) is 500~1000 kDa.

[0027] Example 1 The preparation steps for solid hydrogen formulation double-layer coated particles are as follows: (1) Raw material pretreatment: Magnesium hydride micro powder was ball-milled to a particle size of 1~5μm under anhydrous, oxygen-free, and nitrogen-protected conditions; diatomaceous earth was dried to a moisture content of 0.3%; (2) Powder mixing: Under a nitrogen atmosphere, 34 parts of magnesium hydride micro powder and 18 parts of potassium dihydrogen phosphate were mixed for 9 min. Then, 20 parts of diatomaceous earth, 14 parts of slow-release regulator (stearic acid and palmitic acid in a mass ratio of 1:1) and 7 parts of hydroxypropyl methylcellulose were added in sequence. The mixture was stirred at a speed of 65 r / min for 28 min to obtain composite powder. (3) Dry granulation: The roller pressing dry granulation process is adopted to produce initial particles of 0.5~2mm; (4) Low temperature drying: vacuum drying at 42℃ for 2 hours, under nitrogen atmosphere, then cooling to room temperature; (5) Double-layer gradient coating: fluidized bed coating technology is adopted. First, 6.5% ethyl cellulose ethanol solution is used as the inner hydrophobic coating liquid with a coating thickness of 50~100μm; then, 4% chitosan dilute acetic acid solution is used as the outer hydrophilic coating liquid with a coating thickness of 30~50μm to obtain solid hydrogen preparation double-layer coated particles.

[0028] Example 2 The preparation steps for solid hydrogen formulation double-layer coated particles are as follows: (1) Raw material pretreatment: Magnesium hydride micro powder was ball-milled to a particle size of 1~5μm under anhydrous, oxygen-free, and nitrogen-protected conditions; diatomaceous earth was dried to a moisture content of 0.3%; (2) Powder mixing: Under a nitrogen atmosphere, 30 parts of magnesium hydride micro powder and 22 parts of potassium dihydrogen phosphate were mixed for 8 min. Then, 15 parts of diatomaceous earth, 10 parts of slow-release regulator (stearic acid and palmitic acid in a mass ratio of 1:1) and 5 parts of hydroxypropyl methylcellulose were added in sequence. The mixture was stirred at 50 r / min for 25 min to obtain composite powder. (3) Dry granulation: The roller pressing dry granulation process is adopted to produce initial particles of 0.5~2mm; (4) Low temperature drying: vacuum drying at 40℃ for 2 hours, under nitrogen atmosphere, then cooling to room temperature; (5) Double-layer gradient coating: fluidized bed coating technology is adopted. First, a 5% ethyl cellulose ethanol solution is used as the inner hydrophobic coating liquid with a coating thickness of 50~100μm; then, a 3% chitosan dilute acetic acid solution is used as the outer hydrophilic coating liquid with a coating thickness of 30~50μm to obtain solid hydrogen preparation double-layer coated particles.

[0029] Example 3 The preparation steps for solid hydrogen formulation double-layer coated particles are as follows: (1) Raw material pretreatment: Magnesium hydride micro powder was ball-milled to a particle size of 1~5μm under anhydrous, oxygen-free, and nitrogen-protected conditions; diatomaceous earth was dried to a moisture content of 0.3%; (2) Powder mixing: Under a nitrogen atmosphere, 38 parts of magnesium hydride micro powder and 15 parts of potassium dihydrogen phosphate were mixed for 10 min. Then, 25 parts of diatomaceous earth, 18 parts of slow-release regulator (stearic acid and palmitic acid in a mass ratio of 1:1) and 10 parts of hydroxypropyl methylcellulose were added in sequence. The mixture was stirred at 80 r / min for 30 min to obtain composite powder. (3) Dry granulation: The roller pressing dry granulation process is adopted to produce initial particles of 0.5~2mm; (4) Low temperature drying: vacuum drying at 45℃ for 2 hours, under nitrogen atmosphere, then cooling to room temperature; (5) Double-layer gradient coating: fluidized bed coating technology is adopted. First, an 8% ethyl cellulose ethanol solution is used as the inner hydrophobic coating liquid with a coating thickness of 50~100μm; then, a 5% chitosan dilute acetic acid solution is used as the outer hydrophilic coating liquid with a coating thickness of 30~50μm to obtain solid hydrogen preparation double-layer coated particles.

[0030] Example 4 The preparation steps for solid hydrogen formulation double-layer coated particles are as follows: (1) Raw material pretreatment: Magnesium hydride micro powder was ball-milled to a particle size of 1~5μm under anhydrous, oxygen-free, and nitrogen-protected conditions; diatomaceous earth was dried to a moisture content of 0.3%; (2) Powder mixing: Under a nitrogen atmosphere, 36 parts of magnesium hydride micro powder and 20 parts of potassium dihydrogen phosphate were mixed for 8.5 min. Then, 22 parts of diatomaceous earth, 16 parts of slow-release regulator (stearic acid and palmitic acid in a mass ratio of 1:1) and 8 parts of hydroxypropyl methylcellulose were added in sequence. The mixture was mixed at a speed of 70 r / min for 27 min to obtain composite powder. (3) Dry granulation: The roller pressing dry granulation process is adopted to produce initial particles of 0.5~2mm; (4) Low temperature drying: vacuum drying at 43℃ for 2 hours, under nitrogen atmosphere, then cooling to room temperature; (5) Double-layer gradient coating: fluidized bed coating technology is adopted. First, 7% ethyl cellulose ethanol solution is used as the inner hydrophobic coating liquid with a coating thickness of 50~100μm; then, 4.5% chitosan dilute acetic acid solution is used as the outer hydrophilic coating liquid with a coating thickness of 30~50μm to obtain solid hydrogen preparation double-layer coated particles.

[0031] Comparative Example 1 (Magnesium hydride particle size is too large) The preparation steps for solid hydrogen formulation double-layer coated particles are as follows: (1) Raw material pretreatment: Magnesium hydride micro powder was ball-milled to a particle size of 10-15 μm under anhydrous, oxygen-free, and nitrogen-protected conditions; diatomaceous earth was dried to a moisture content of 0.3%; (2) Powder mixing: Under a nitrogen atmosphere, 34 parts of magnesium hydride micro powder and 18 parts of potassium dihydrogen phosphate were mixed for 9 min. Then, 20 parts of diatomaceous earth, 14 parts of slow-release regulator (stearic acid and palmitic acid in a mass ratio of 1:1) and 7 parts of hydroxypropyl methylcellulose were added in sequence. The mixture was stirred at a speed of 65 r / min for 28 min to obtain composite powder. (3) Dry granulation: The roller pressing dry granulation process is adopted to produce initial particles of 1~2mm; (4) Low temperature drying: vacuum drying at 42℃ for 2 hours, under nitrogen atmosphere, then cooling to room temperature; (5) Double-layer gradient coating: fluidized bed coating technology is adopted. First, 6.5% ethyl cellulose ethanol solution is used as the inner hydrophobic coating liquid with a coating thickness of 50~100μm; then, 4% chitosan dilute acetic acid solution is used as the outer hydrophilic coating liquid with a coating thickness of 30~50μm to obtain solid hydrogen preparation double-layer coated particles.

[0032] Comparative Example 2 (lacking sustained-release modifier) The preparation steps for solid hydrogen formulation double-layer coated particles are as follows: (1) Raw material pretreatment: Magnesium hydride micro powder was ball-milled to a particle size of 1~5μm under anhydrous, oxygen-free, and nitrogen-protected conditions; diatomaceous earth was dried to a moisture content of 0.3%; (2) Powder mixing: Under a nitrogen atmosphere, 34 parts of magnesium hydride micro powder and 18 parts of potassium dihydrogen phosphate were mixed for 9 min, and then 20 parts of diatomaceous earth and 7 parts of hydroxypropyl methylcellulose were added in sequence. The mixture was mixed at a speed of 65 r / min for 28 min to obtain composite powder. (3) Dry granulation: The roller pressing dry granulation process is adopted to produce initial particles of 1~2mm; (4) Low temperature drying: vacuum drying at 42℃ for 2 hours, under nitrogen atmosphere, then cooling to room temperature; (5) Double-layer gradient coating: fluidized bed coating technology is adopted. First, 6.5% ethyl cellulose ethanol solution is used as the inner hydrophobic coating liquid with a coating thickness of 50~100μm; then, 4% chitosan dilute acetic acid solution is used as the outer hydrophilic coating liquid with a coating thickness of 30~50μm to obtain solid hydrogen preparation double-layer coated particles.

[0033] Comparative Example 3 (single-layer coating, without outer chitosan layer) The preparation steps for solid hydrogen formulation monolayer coated particles are as follows: (1) Raw material pretreatment: Magnesium hydride micro powder was ball-milled to a particle size of 1~5μm under anhydrous, oxygen-free, and nitrogen-protected conditions; diatomaceous earth was dried to a moisture content of 0.3%; (2) Powder mixing: Under a nitrogen atmosphere, 34 parts of magnesium hydride micro powder and 18 parts of potassium dihydrogen phosphate were mixed for 9 min. Then, 20 parts of diatomaceous earth, 14 parts of slow-release regulator (stearic acid and palmitic acid in a mass ratio of 1:1) and 7 parts of hydroxypropyl methylcellulose were added in sequence. The mixture was stirred at a speed of 65 r / min for 28 min to obtain composite powder. (3) Dry granulation: The roller pressing dry granulation process is adopted to produce initial particles of 1~2mm; (4) Low temperature drying: vacuum drying at 42℃ for 2 hours, under nitrogen atmosphere, then cooling to room temperature; (5) Single-layer coating: Fluidized bed coating technology is used, with 6.5% ethyl cellulose ethanol solution as the hydrophobic coating liquid, and the coating thickness is 50~100μm; no outer chitosan coating is added, and solid hydrogen preparation single-layer coated particles are obtained.

[0034] Comparative Example 4 (Coating thickness too thin) The preparation steps for solid hydrogen formulation double-layer coated particles are as follows: (1) Raw material pretreatment: Magnesium hydride micro powder was ball-milled to a particle size of 1~5μm under anhydrous, oxygen-free, and nitrogen-protected conditions; diatomaceous earth was dried to a moisture content of 0.3%; (2) Powder mixing: Under a nitrogen atmosphere, 34 parts of magnesium hydride micro powder and 18 parts of potassium dihydrogen phosphate were mixed for 9 min. Then, 20 parts of diatomaceous earth, 14 parts of slow-release regulator (stearic acid and palmitic acid in a mass ratio of 1:1) and 7 parts of hydroxypropyl methylcellulose were added in sequence. The mixture was stirred at a speed of 65 r / min for 28 min to obtain composite powder. (3) Dry granulation: The roller pressing dry granulation process is adopted to produce initial particles of 1~2mm; (4) Low temperature drying: vacuum drying at 42℃ for 2 hours, under nitrogen atmosphere, then cooling to room temperature; (5) Double-layer gradient coating: Fluidized bed coating technology is used. First, a 6.5% ethyl cellulose ethanol solution is used as the inner hydrophobic coating liquid with a coating thickness of 15~25μm. Then, a 4% chitosan dilute acetic acid solution is used as the outer hydrophilic coating liquid with a coating thickness of 10~15μm to obtain solid hydrogen preparation double-layer coated particles.

[0035] I. Performance Testing Methods Test 1: Determination of Particle Physical Properties Particle size distribution: 200 particles were randomly selected and sieved using the standard sieve method (sieve openings of 0.5, 1.0, 1.5, and 2.0 mm). The mass of material on each sieve was weighed, and the particle size distribution was calculated.

[0036] Bulk density: Fill a 10mL graduated cylinder with the particles naturally, weigh the mass, and calculate the bulk density (g / mL).

[0037] Angle of repose: Using the fixed funnel method, the particles fall naturally, and the angle between the inclined plane of the cone and the horizontal plane is measured.

[0038] Friability: Take 5.0g of particles and place them in a friability tester. Rotate the tester at 25r / min for 4min. Take them out and pass them through a 0.5mm sieve. Weigh the mass of the material on the sieve. Calculate the friability (%) = (mass before rotation - mass of the material on the sieve after rotation) / mass before rotation × 100%.

[0039] Test 2: Packaging Quality Inspection Coating thickness: Ten particles were randomly selected, cut radially, and the coating thickness of the inner layer (ethyl cellulose) and outer layer (chitosan) was measured by scanning electron microscopy (SEM), and the average value was taken.

[0040] Coating uniformity: Four measurement points were taken for the same particle along different directions, and the coefficient of variation (CV, %) of coating thickness was calculated. CV = standard deviation / mean × 100%.

[0041] Coating rate: Weigh 2.0g of coated particles, place them in 50mL of anhydrous ethanol, sonicate for 5min to dissolve the ethyl cellulose layer, filter to collect the residue, vacuum dry at 60℃ for 2h and weigh; then dissolve the chitosan layer with 1% acetic acid solution, treat and weigh in the same way; calculate the total coating weight gain (%) = (mass after coating - initial particle mass before coating) / initial particle mass before coating × 100%.

[0042] Test 3: Measurement of cumulative hydrogen release amount and hydrogen release rate Methods: Weigh 2.0 g of double-layer coated solid hydrogen preparation particles and place them in a 500 mL sealed reaction flask. Add 200 g of simulated soil (sandy loam soil passed through a 40-mesh sieve, initial pH 6.5) with a moisture content of 25% (mass fraction). After sealing, connect the flask to a gas flow meter (range 0~500 mL, accuracy 0.1 mL) via a gas delivery tube. Place the reaction flask in a constant temperature incubator at 25±1℃. Record the cumulative hydrogen release (mL) at 1d, 3d, 5d, 7d, 10d, and 14d, and calculate the average hydrogen release rate (mL / g / d) for each time period. Each group was replicated in triplicate.

[0043] Test 4: pH Response Test Methods: Prepare phosphate-borate buffer solutions (0.05 mol / L) with pH values ​​of 5.0, 6.0, 7.0, 8.0, and 9.0. Take 100 mL of each solution and place it in a 250 mL sealed reaction flask. Add 1.0 g of double-layer coated particles and incubate at 25 ± 1 °C. Record the cumulative hydrogen release over 24 h and calculate the hydrogen release rate ratio (%) relative to the pH 7.0 condition. Perform three replicates per group.

[0044] Test 5: Reversibility test of pH response of chitosan outer layer Methods: 1.0 g of double-layer coated particles were immersed in 100 mL of pH 9.0 buffer for 2 h (simulating alkaline conditions), then transferred to pH 6.5 buffer for 2 h (simulating pH recovery). This cycle was repeated 3 times, and the hydrogen release rate was measured 24 h after each cycle. The hydrogen release rate under the initial pH 6.5 condition was taken as 100%, and the hydrogen release rate recovery rate (%) for each cycle was calculated. Each group was divided into 3 replicates.

[0045] Test 6: Measurement of water permeation rate Methods: Weigh 1.0 g of double-layer coated granules and place them above a sealed desiccator containing 50 mL of distilled water (without direct contact with the water surface, only through water vapor permeation). Maintain the temperature at 25 ± 1 °C. Remove the granules at 2 h, 6 h, 12 h, 24 h, and 48 h, and quickly weigh them to measure the weight gain. Calculate the cumulative water permeation (mg / g). Simultaneously measure the weight of single-layer coated granules (ethyl cellulose layer only) and Comparative Example 4 (thin coating) as controls. Each group had 3 replicates.

[0046] Test 7: Particle integrity and storage stability Accelerated stability testing: 10.0g of double-layer coated particles were sealed in an aluminum foil bag and placed in a constant temperature and humidity chamber at 25℃ (room temperature control) and 40℃ / 75%RH (accelerated conditions), respectively. The particles were removed at 0d, 7d, 14d, and 30d, and the cumulative hydrogen release (mL / g) over 7 days was measured. The hydrogen release retention rate (%) relative to 0d was calculated, and the appearance of the particles was observed for any damage, swelling, or adhesion.

[0047] Each group has 3 repetitions.

[0048] II. Performance Test Data Table 1. Physical properties of particles

[0049] As can be seen from Table 1, the friability of Examples 1-4 and Comparative Examples 1, 3, and 4 is all <5%, indicating good formability; Comparative Example 2 has a friability of 5.8% and the lowest bulk density (0.65 g / mL), lacking the hydrophobic bonding and filling effect of stearic acid / palmitic acid, resulting in weak interparticle bonding and loose particles.

[0050] Table 2 Coating Quality

[0051] As shown in Table 2, Examples 1-4 had inner layer CVs of 11.8%-22.1% and outer layer CVs of 11.1%-20.0%, indicating good coating uniformity; Example 3 showed the best uniformity (CV 11.8% / 11.1%). Comparative Example 4 had an inner layer CV of 25.0% and an outer layer CV of 33.3%, indicating that the coating was too thin, leading to a significant decrease in uniformity; the total coating weight gain was only 3.8%, indicating severely insufficient coating amount. Comparative Example 3, lacking an outer chitosan layer, had a total coating weight gain of 7.5%, only about 60% of that of a double-layer coating.

[0052] Depend on Figure 1-2It can be seen that Examples 1-4 exhibit a rapid initial release followed by a slower, sustained, and stable supply curve, accumulating 362-398 mL / g over 14 days. The hydrogen release rate was 20-24.3 mL / g / d from days 7-10, and 14.3-17.5 mL / g / d from days 10-14, showing a gradual decline. In Comparative Example 1, the hydrogen release rate was only 208 mL / g over 14 days, 57.5% of that in Example 1, indicating low reactivity due to a smaller specific surface area. In Comparative Example 2, a large amount of H2 was released at 85 mL / g / d from day 0-1, decreasing to 7.7 after 7 days, and only 295 mL / g at day 14, indicating significant initial H2 loss and waste. In Comparative Example 3, the hydrogen release rate was 78 mL / g / d from day 0-1, decreasing to 6.7 after 7 days, similar to the trend in Comparative Example 2; lacking a chitosan pH-responsive layer, the hydrogen release lacked self-regulating ability. In Comparative Example 4, a large amount of 95 mL / g / d was released from 0 to 1 day, but only 5.7 after 7 days and only 290 mL / g after 14 days.

[0053] Table 3 pH responsiveness - relative ratio of hydrogen release rate over 24 h under different pH conditions (%)

[0054] As shown in Table 3, the hydrogen release rate of Examples 1-4 significantly decreased to 28%-62% at pH 8.0-9.0, indicating that the pH negative feedback self-regulation of the chitosan outer layer was effective: alkaline deprotonation and contraction → decreased permeability → self-inhibition of hydrogen release. In Comparative Example 3, the rate remained at 95% at pH 9.0, with almost no pH response, demonstrating that the chitosan outer layer is the core of the pH self-regulation function. In Comparative Example 1, the rate was 55% at pH 9.0, indicating insufficient pH response trigger signal due to low reactivity, slow alkali production.

[0055] Table 4. Reversibility of pH response of chitosan outer layer - recovery rate of hydrogen release rate after pH cycle switching (%)

[0056] Note: Comparative Example 3, lacking a chitosan outer layer, exhibits extremely weak pH responsiveness and is almost unaffected by pH changes, thus its recovery rate is meaninglessly close to 100%. Comparative Example 4, with its thin coating layer, shows a significant decrease in recovery rate after three cycles, indicating insufficient durability of the coating structure.

[0057] As shown in Table 4 above, the recovery rate after three pH cycles in Examples 1-4 was 84%-87%, indicating good reversibility of chitosan's pH-responsive shrinkage-swelling. In Comparative Example 4, the recovery rate was only 74.2% after three cycles, mainly due to structural fatigue damage caused by repeated shrinkage and expansion of the thin coating layer.

[0058] Depend on Figure 3As can be seen, in Examples 1-4, the water permeation rate after 48 hours was 82.5-95.5 mg / g, which was moderate and controllable. This was mainly due to the synergistic water-blocking effect of the hydrophobic barrier of the inner layer of ethyl cellulose and the slow-release regulator. In the comparative example, the permeation rate after 448 hours was 158 mg / g, indicating that the coating layer was too thin, resulting in severely insufficient water-blocking ability. In Comparative Example 2, the permeation rate after 48 hours was 125 mg / g, indicating that the lack of hydrophobic stearic acid / palmitic acid filler led to excessively rapid water permeation. In Comparative Example 3, the permeation rate after 48 hours was 118.5 mg / g, mainly because the absence of the chitosan outer layer resulted in a larger water permeation channel.

[0059] Table 5 Accelerated Storage Stability - 7-day Cumulative Hydrogen Release Retention Rate (%)

[0060] As shown in Table 5 above, Examples 1-4 exhibited a hydrogen release retention rate of >92% after 30 days under accelerated conditions of 40℃ / 75%RH. This was mainly due to the effective isolation of environmental moisture by the hydrophobic barrier of ethyl cellulose, and the further reduction of moisture permeation by the slow-release regulator, resulting in excellent storage stability. In contrast, Comparative Example 4 showed a retention rate of only 62.8% after 30 days of accelerated conditions, indicating that the coating layer was insufficient to block environmental moisture, leading to the continuous and slow hydrolysis and consumption of MgH2. Comparative Example 2 showed a retention rate of 68.5% after 30 days of accelerated conditions, with the absence of stearic acid / palmitic acid resulting in unobstructed internal moisture channels. Comparative Example 1, however, demonstrated the best stability due to the low reactivity of MgH2, resulting in slow hydrolysis even under moisture permeation conditions.

[0061] Example 5 The preparation method of the γ-PGA (polyglutamic acid) / melatonin composite controlled-release material is as follows: S1. Dissolve melatonin in anhydrous ethanol to prepare a melatonin ethanol solution with a concentration of 150 μmol / L; S2. Immerse 10.0g of γ-PGA powder in 500mL of melatonin ethanol solution and stir magnetically for 30min; S3. Vacuum drying at 30℃ for 6 hours allows ethanol to evaporate completely, melatonin to be uniformly dispersed and physically embedded in the γ-PGA matrix; S4. Grind through a 100-mesh sieve to obtain γ-PGA / melatonin composite controlled-release material powder.

[0062] Example 6 A pH / Mg 2+ The responsive controlled-release hydrogen-melatonin complex formulation was prepared by mixing the solid hydrogen formulation double-layer coated particles prepared in Example 3, the γ-PGA / melatonin complex controlled-release material prepared in Example 5, and gelatin at a mass ratio of 3:1:0.15, and compressing them into integrated particles with a diameter of 2-3 mm under a pressure of 10 MPa.

[0063] Example 7 A pH / Mg2+ The responsive controlled-release hydrogen-melatonin complex formulation was prepared by mixing the solid hydrogen formulation double-layer coated particles prepared in Example 3, the γ-PGA / melatonin complex controlled-release material prepared in Example 5, and gelatin at a mass ratio of 4:1:0.15, and compressing them into integrated particles with a diameter of 2-3 mm under a pressure of 10 MPa.

[0064] Example 8 A pH / Mg 2+ The responsive controlled-release hydrogen-melatonin complex formulation was prepared by mixing the solid hydrogen formulation double-layer coated particles prepared in Example 3, the γ-PGA / melatonin complex controlled-release material prepared in Example 5, and gelatin at a mass ratio of 5:1:0.15, and compressing them into integrated particles with a diameter of 2-3 mm under a pressure of 10 MPa.

[0065] Comparative Example 5 A pH / Mg 2+ The responsive controlled-release hydrogen-melatonin complex formulation was prepared by mixing the solid hydrogen formulation double-layer coated particles prepared in Comparative Example 1, the γ-PGA / melatonin complex controlled-release material prepared in Example 5, and gelatin at a mass ratio of 4:1:0.15, and compressing them into integrated particles with a diameter of 2-3 mm under a pressure of 10 MPa.

[0066] Comparative Example 6 A pH / Mg 2+ The responsive controlled-release hydrogen-melatonin complex formulation was prepared by mixing the solid hydrogen formulation double-layer coated particles prepared in Comparative Example 2, the γ-PGA / melatonin complex controlled-release material prepared in Example 5, and gelatin at a mass ratio of 4:1:0.15, and compressing them into integrated particles with a diameter of 2-3 mm under a pressure of 10 MPa.

[0067] Comparative Example 7 A pH / Mg 2+ The responsive controlled-release hydrogen-melatonin complex formulation was prepared by mixing the solid hydrogen formulation double-layer coated particles prepared in Comparative Example 3, the γ-PGA / melatonin complex controlled-release material prepared in Example 5, and gelatin at a mass ratio of 4:1:0.15, and compressing them into integrated particles with a diameter of 2-3 mm under a pressure of 10 MPa.

[0068] Comparative Example 8 A pH / Mg 2+ The responsive controlled-release hydrogen-melatonin complex formulation was prepared by mixing the solid hydrogen formulation double-layer coated particles prepared in Comparative Example 4, the γ-PGA / melatonin complex controlled-release material prepared in Example 5, and gelatin at a mass ratio of 4:1:0.15, and compressing them into integrated particles with a diameter of 2-3 mm under a pressure of 10 MPa.

[0069] Performance testing: Test 8: Synchronicity of Hydrogen Release and MT Release in Compound Formulation Synchronization Index (SI): The Pearson correlation coefficient between H2 release and MT release at different time periods is measured. The closer the SI is to 1, the better the synchronicity. Test 9: Mg 2+ Slow-release damping effect Methods: The hydrogen release curves of the compound formulation in simulated soil were determined, the coefficient of variation (CV) of the hydrogen release rate was calculated, and the Mg content was evaluated. 2+ Contribution of cross-linking damping to hydrogen release stability Test 10: Dynamics of H2 and MT concentrations in the root zone after application of compound formulations to soil Methods: 5.0 g of the compound preparation was buried in 1 kg of sandy loam soil with a moisture content of 25% (simulating root zone soil) and kept at a constant temperature of 25±1℃. Soil gas and soil solution samples were collected at 1, 3, 5, 7, 10, 14, 21, and 28 days. The H2 concentration (gas chromatography) and MT concentration (HPLC-fluorescence detection) were determined. Table 6. Cumulative hydrogen release of compound formulations (mL / g, based on total formulation mass)

[0070] Note: The proportion of solid hydrogen particles in the total mass of the compound formulation varies. For ease of comparison, the hydrogen release is uniformly converted to the cumulative hydrogen release per gram of total formulation. Examples 7-8 have a higher proportion of hydrogen particles, resulting in a higher hydrogen release than Example 6.

[0071] Table 7. Average hydrogen release rate of the compound formulation at different time periods (mL / g / d)

[0072] As can be seen from Tables 6-7 above, Examples 6-8 exhibit ideal curves of initial stability followed by a gradual slowdown and long-term stability. The cumulative hydrogen release over 28 days was 462-525 mL / g, maintaining 11-11.4 mL / g / d from days 14 to 21, and 8.1-8.6 mL / g / d from days 21 to 28, showing extremely gradual decline. Example 7 showed a rate of 30 mL / g / d from days 3 to 5, and 29 mL / g / d from days 5 to 7, with a prolonged peak plateau and minimal fluctuation (CV < 5%), indicating that Mg... 2+ Crosslinking damping effectively suppressed rate oscillations. In contrast, in Comparative Examples 6-8, the rate plummeted to <8 mL / g / d after 7 days, accumulating to only 285~295 mL / g over 28 days, and almost stopped in the later stages.

[0073] Table 8. pH responsiveness of the compound formulation (relative ratio of hydrogen release over 24 hours, %)

[0074] As shown in Table 8, the hydrogen release of Examples 6-8 decreased to 20%-25% at pH 9.0, a further reduction compared to the 28%-36% in Examples 1-4, indicating that the Mg of γ-PGA... 2+ Crosslinking shrinkage and chitosan pH shrinkage produce a synergistic enhancing effect, and the dual barrier further reduces permeability under alkaline conditions. In contrast, Comparative Example 5 exhibits a weak pH response signal due to slow alkali production.

[0075] Table 9. Synchronicity of γ-PGA water absorption, swelling, and MT release

[0076] As shown in Table 9, the H2-MT release synchronization index (SI) of Examples 6-8 reached 0.92-0.94, indicating a high degree of synchronization. Hydrogen release and MT release accelerated synchronously with increasing humidity (an increase of 28%-36%), naturally matching the physiological rhythm of increased plant transpiration and the need for stress resistance. In contrast, Comparative Examples 6 and 7, due to defects in the basic particle coating, experienced excessively rapid water penetration and premature oversaturation and expansion of γ-PGA, resulting in excessively rapid MT release (60%-64% release in 14 days) and decreased synchronization.

[0077] Table 10 Dynamics of H2 and MT concentrations in root zone soil (Example 7, after application)

[0078] As shown in Table 10, the H2 concentration peaked at 5 days (245 μL / L) and then slowly decreased, maintaining an effective concentration of 125 μL / L at 28 days without drastic fluctuations; the MT concentration peaked at 7 days (39 ng / mL) and then decreased slowly in sync with H2, with a correlation coefficient r=0.97 between the two concentration curves; the soil pH remained within the safe range of 6.6~7.1 throughout the process without any abnormal increase, indicating that the pH negative feedback + potassium dihydrogen phosphate buffer system was effective.

[0079] When the above-mentioned compound preparation is applied to chrysanthemum cultivation, different chrysanthemum varieties may exhibit genotypic differences in their response to the H2-MT compound preparation. Therefore, this invention selects four representative medicinal chrysanthemum varieties to verify the broad-spectrum applicability of the preparation, without making direct cross-varietal comparisons.

[0080] Conditions: During the high-temperature period of summer (average daily temperature 35℃), the medicinal chrysanthemum variety "Hangzhou White Chrysanthemum" is used. Treatment: Example 7 compound preparation, 2.5g per plant, applied to the root zone, once every 7 days.

[0081] Application Example 2: Drought Stress Relief Conditions: Water control simulates drought stress (soil moisture content drops to 40% of field capacity), using the medicinal chrysanthemum variety "Boju"; Treatment: Example 7 compound preparation, 3g per plant, applied to the root zone, once every 10 days.

[0082] Application Example 3: Salt Stress Relief Conditions: NaCl stress (100 mmol / L), medicinal chrysanthemum variety "Chuju"; Treatment: Example 7 compound preparation, 2g per plant, applied to the root zone, once every 7 days.

[0083] Application Example 4: Combined stress (high temperature + drought) Conditions: High temperature (average daily temperature 38℃) + controlled watering (soil moisture content 45%), medicinal chrysanthemum variety "Huaiju"; Treatment: Example 7 compound preparation, 3g per plant, applied to the root zone, once every 5 days.

[0084] Application Comparative Example 1: Water Control (Blank Control) Conditions: Same drought stress as in Application Example 2; Treatment: Equal volume of water, no pre-prepared agents applied.

[0085] Application Comparative Example 2: Irrigation with hydrogen-rich water only Conditions: Same high-temperature stress as in Application Example 1; Treatment: Hydrogen-rich water (saturated concentration, approximately 1.6 mg / L), 200 mL / plant each time, once every 3 days.

[0086] Application Comparative Example 3: Foliar spraying of exogenous MT alone Conditions: Same high-temperature stress as in Application Example 1; Treatment: Apply MT solution (100 μmol / L) as a foliar spray, 50 mL per plant each time, once every 3 days.

[0087] Application Comparative Example 4: Simple Physical Mixture of H2+MT Conditions: Same combined stress as in Application Example 4; Treatment: Magnesium hydride micro powder (uncoated) + MT ethanol solution, calculated according to the equivalent H2 / MT amount in Example 7, are simply mixed and applied to the root zone.

[0088] Application Comparison Example 5: Conventional Fertilizer + Pesticide Control Conditions: Same drought stress as in Application Example 2 Treatment: Apply conventional NPK compound fertilizer (15-15-15) + paclobutrazol drought resistant agent, according to local standard dosage.

[0089] Application of Comparative Example 6: Comparative Example 6 compound formulation Conditions: Same high-temperature stress as in Application Example 1 Treatment: Comparative Example 6 compound formulation (made from basic granules lacking sustained-release regulators), 2.5g per plant.

[0090] Application Comparative Example 7: Solid hydrogen formulation only (without MT component) Conditions: Same high-temperature stress as in Application Example 1 Treatment: Example 3 Solid hydrogen preparation double-layer coated particles (without γ-PGA / MT), 2g per plant.

[0091] Each application example (Application Examples 1-4) is equipped with an independent stress environment control group, namely "the water control under this stress condition", which specifically includes: high temperature stress water control (corresponding to Application Example 1), drought stress water control (corresponding to Application Example 2), salt stress water control (corresponding to Application Example 3) and combined stress water control (corresponding to Application Example 4).

[0092] Pot Experiment Protocol and Measurement Indicators

[0093] Pot specifications: 25cm in diameter, 30cm in height, filled with 5kg of sandy loam soil. Each treatment consisted of 10 plants, with 3 replicates, arranged in a randomized block design. Pre-cultured for 14 days before stress treatment (normal management).

[0094]

[0095] Data Results Table 11 Physiological indicators of chrysanthemum under different stresses (stress for 14 days)

[0096] As shown in Table 11 above, under high-temperature stress, Application Example 1 showed a 124.5% increase in net photosynthetic rate (Pn), a 67.9% decrease in MDA, a 96.7% increase in SOD, a 266.4% increase in endogenous MT, and a 225% increase in SNAT expression compared to the corresponding water control (independent setting). Application Example 2 showed moderate effects but required frequent application; Application Example 3 was effective in direct antioxidant action but could not induce endogenous MT synthesis; Application Example 4, due to the burst release of H2 and rapid MT loss, was even less effective than hydrogen-rich water alone. Exogenous MT upregulated SNAT expression through positive feedback, further promoting endogenous MT synthesis, forming a cascade amplification effect of H2→SNAT↑→endogenous MT↑→SNAT↑↑.

[0097] Table 12 Physiological indicators of chrysanthemum under drought stress (21 days of stress)

[0098] As can be seen from Table 12 above, in application example 2, γ-PGA dehydration and shrinkage under drought conditions, and the release of hydrogen and MT automatically slows down, achieving "on-demand supply".

[0099] Table 13. Chrysanthemum yield and quality under various treatments under combined stress (harvest period)

[0100] As can be seen from Table 13 above, in Application Example 4, the yield of dried flowers under combined stress reached 89.1% of that under normal management without stress, and the total flavonoid content reached 95.1%, with the quality approaching normal levels.

[0101] Table 14 Verification of the universality of Example 7 under different stress types

[0102] As can be seen from Table 14 above, the compound preparation in Example 7 showed significant improvement under different stress types, with the best effect under high temperature stress (H2-MT heat shock response pathway was most fully activated), and the effect under salt stress was relatively mild but still significant, demonstrating good broad-spectrum stress resistance and adaptability.

[0103] The above description is merely a preferred embodiment of the present invention and is not intended to limit the invention in any other way. Any person skilled in the art may make changes or modifications to the above-disclosed technical content to create equivalent embodiments. However, any simple modifications, equivalent changes, and modifications made to the above embodiments based on the technical essence of the present invention without departing from the scope of the present invention shall still fall within the protection scope of the present invention.

Claims

1. A pH / Mg 2+ A responsive controlled-release hydrogen-melatonin complex formulation, characterized in that, The composite formulation is made by mixing solid hydrogen formulation double-layer coated particles, γ-PGA / melatonin composite controlled-release material and biocompatible binder in a mass ratio of 3~5:1:0.1~0.2, and then forming integrated particles with a diameter of 2~3mm by low-pressure tableting process.

2. A pH / Mg solution according to claim 1 2+ A responsive controlled-release hydrogen-melatonin complex formulation, characterized in that, The preparation steps of the solid hydrogen preparation double-layer coated particles are as follows: (1) Raw material pretreatment: Magnesium hydride micro powder was ball-milled to a particle size of 1~5μm under anhydrous, oxygen-free, and nitrogen-protected conditions; diatomaceous earth was dried to a moisture content of ≤0.5%; (2) Powder mixing: Under a nitrogen atmosphere, first mix 30-38 parts of magnesium hydride micro powder with 15-22 parts of potassium dihydrogen phosphate for 8-10 min, then add 15-25 parts of diatomaceous earth, 10-18 parts of slow-release regulator and 5-10 parts of binder in sequence, and mix at a speed of 50-80 r / min for 25-30 min to obtain composite powder; (3) Dry granulation: The roller pressing dry granulation process is adopted to produce initial particles of 0.5~2mm; (4) Low temperature drying: vacuum drying at 40~45℃ for 2 hours under nitrogen atmosphere, then cooling to room temperature; (5) Double-layer gradient coating: Fluidized bed coating technology is adopted. First, ethyl cellulose ethanol solution is used as the inner hydrophobic coating liquid with a coating thickness of 50~100μm; then, chitosan dilute acetic acid solution is used as the outer hydrophilic coating liquid with a coating thickness of 30~50μm to obtain solid hydrogen preparation double-layer coated particles.

3. A pH / Mg solution according to claim 2 2+ A responsive controlled-release hydrogen-melatonin complex formulation, characterized in that, The slow-release regulator in step (2) is a mixture of stearic acid and palmitic acid; the binder is hydroxypropyl methylcellulose.

4. A pH / Mg solution according to claim 3 2+ A responsive controlled-release hydrogen-melatonin complex formulation, characterized in that, The mass ratio of stearic acid to palmitic acid is 1:

1.

5. A pH / Mg solution according to claim 2 2+ A responsive controlled-release hydrogen-melatonin complex formulation, characterized in that, The mass fraction of the ethyl cellulose ethanol solution in step (5) is 5-8%; the mass fraction of the chitosan dilute acetic acid solution is 3-5%.

6. A pH / Mg solution according to claim 1 2+ A responsive controlled-release hydrogen-melatonin complex formulation, characterized in that, The preparation method of the γ-PGA / melatonin composite controlled-release material is as follows: S1. Dissolve melatonin in anhydrous ethanol to prepare a melatonin ethanol solution with a concentration of 100~200 μmol / L; S2. Immerse γ-PGA powder in melatonin ethanol solution and stir for 30 min; S3. Vacuum dry at 30~35℃ for 6-7h to allow ethanol to evaporate completely, melatonin to be uniformly dispersed and physically embedded in the γ-PGA matrix; S4. Grind through a 100-mesh sieve to obtain γ-PGA / melatonin composite controlled-release material powder.

7. A pH / Mg solution according to claim 6 2+ A responsive controlled-release hydrogen-melatonin complex formulation, characterized in that, The liquid-to-solid ratio of melatonin ethanol solution to γ-PGA in S2 is 40-60 mL / g.

8. A pH / Mg solution according to claim 1 2+ A responsive controlled-release hydrogen-melatonin complex formulation, characterized in that, The biocompatible adhesive is gelatin.

9. The pH / Mg according to any one of claims 1 to 8 2+ Application of a responsive controlled-release hydrogen-melatonin complex formulation in alleviating abiotic stress in chrysanthemum.

10. The application according to claim 9, characterized in that, The application method is as follows:

1. Application timing: Apply every 7-10 days from the time the chrysanthemum is planted until the budding stage; during the flowering period and the period of high temperature and strong light stress, apply every 5-7 days.

2. Application method: Dig a shallow trench 5-10cm deep, 5-8cm away from the base of the chrysanthemum plant, spread the granules evenly in, cover with soil and compact.

3. Application rate: Apply 2-3g per chrysanthemum plant each time; 4. pH monitoring and adjustment: Regularly use a portable pH meter to test the pH of the root zone soil. When the soil pH is >8.0, reduce the application amount or suspend application. Resume application after the soil pH returns to 6.0~7.0.